2017
DOI: 10.1039/c7ra06404g
|View full text |Cite
|
Sign up to set email alerts
|

Novel poly(aniline-co-3-amino-4-methoxybenzoic acid) copolymer for the separation and recovery of Pd(ii) from the leaching liquor of automotive catalysts

Abstract: The PANI–AMB copolymers were prepared and used for separation and recovery palladium from the leaching solutions of the automotive catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Based on the principle of the minimum charge density, the charge density of Pd(CN) 4 2− is less than those of Co(CN) 6 3− and Fe(CN) 6 3− . Fewer water molecules are required to stabilize Pd(CN) 4 2− compared to multivalent anions in the aqueous solution [ 59 , 60 ]. Pd(CN) 4 2− possibly exhibited higher affinity for hydrophobic quaternary ammonium compared to Co(CN) 6 3− or Fe(CN) 6 3− .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the principle of the minimum charge density, the charge density of Pd(CN) 4 2− is less than those of Co(CN) 6 3− and Fe(CN) 6 3− . Fewer water molecules are required to stabilize Pd(CN) 4 2− compared to multivalent anions in the aqueous solution [ 59 , 60 ]. Pd(CN) 4 2− possibly exhibited higher affinity for hydrophobic quaternary ammonium compared to Co(CN) 6 3− or Fe(CN) 6 3− .…”
Section: Resultsmentioning
confidence: 99%
“…A stock solution of 10.00 g·L –1 [PdCl 4 ] 2– was prepared following the literature. 44 Concentration of working of palladium solution can be obtained by diluting the standard stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…The morphology and EDS analyses of palladium after deposition were carried out by SEM (Nova NanoSEM, Thermo Scientific, Waltham, USA), and the valence of palladium on the surface of coating was analyzed by XPS (K-Alpha + , Thermo USA) and HRTEM (JEM-210, JEOL, Tokyo, Japanese). 44 Concentration of working of palladium solution can be obtained by diluting the standard stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a new peak assigned to S-Pd bonds appeared at 162.44 eV [ 36 ]. The peaks at 337.43 eV and 342.67 eV were ascribed to the Pd-Cl bonds in PdCl 4 2− , and the doublet peaks (BE = 338.21 eV, 343.36 eV) likely corresponded to the binding energies of Pd-N or Pd-S bonds ( Figure 2 d) [ 37 , 38 , 39 ]. The XPS results further confirmed that DMTD was successfully grafted onto the PS-Cl and also indicated that Pd (II) coordinated with the N and S atoms in the PS-DMTD absorbent.…”
Section: Resultsmentioning
confidence: 99%